Long-Term Survival in a Patient with Multiple Brain Metastases from Small-Cell Lung Cancer Treated with Gamma Knife Radiosurgery on Four Occasions: A Case Report - Ameer L. Elaimy; Sudheer R. Thumma; Andrew F. Lamm; Alexander R. Mackay; Wayne T. Lamoreaux; Robert K. Fairbanks; John J. Demakas; Barton S. Cooke; Christopher M. Lee (Case Reports in Neurological Medicine)
Brain metastases are the most common cancerous neoplasm in the brain. The treatment of these lesions is challenging and often includes a multimodality management approach with whole-brain radiation therapy, stereotactic radiosurgery, and neurosurgery options. Although advances in biomedical imaging technologies and the treatment of extracranial cancer have led to the overall increase in the survival of brain metastases patients, the finding that select patients survive several years remains puzzling. For this reason, we present the case of a 70-year-old patient who was diagnosed with multiple brain metastases from small-cell lung cancer five years ago and is currently alive following treatment with chemotherapy for the primary cancer and whole-brain radiation therapy and Gamma Knife radiosurgery on four separate occasions for the neurological cancer. Since the diagnosis of brain metastases five years ago, the patient’s primary cancer has remained controlled. Furthermore, multiple repeat GKRS procedures provided this patient with high levels of local tumor control, which in combination with a stable primary cancer led to an extended period of survival and a highly functional life. Further analysis and clinical research will be valuable in assessing the durability of multiple GKRS for brain metastases patients who experience long-term survival.